Medical microbiology - Murray, Patrick R.; Pfaller, Michael A.; Rosenthal, Ken S. (Elsevier, 2016)
Turn to Medical Microbiology, 8th Edition for a thorough, clinically relevant understanding of microbes and their diseases. This succinct, easy-to-use text presents the fundamentals of microbiology and immunology in a clearly written, engaging manner-effectively preparing you for your courses, exams, and beyond